Effect of temperature on physiological responses of Peruvian scallop Argopecten purpuratus - Dionicio Acedo, Jhon (2015)
The effect of temperature on the clearance rate (CR), ingestion rate (IR) and specific oxygen consumption (SOC) in individuals of Argopecten purpuratus at different size groups were determined. The CR and IR tests were performed at a concentration of approximately 1x106 cel.mlL-1 of Chaetoceros calcitrans, two temperatures 17 and 22 °C were evaluated and different groups of average size were formed of 7.6 ± 0.265, and 0.058 ± 4.9 3.7 ± 0.173 cm. In SOC test the average size groups were 8.1 ± 0.351, 0.058 ± 5.6 and 4.3 ± 0.100 cm. The results show a significant effect of temperature in CR (Lh-1) and IR (cel.h-1 x 105) on the larger individuals (7.6 ± 0.265 cm), it was observed at 22 °C an average increase, about 17 °C, up to 250% to CR and 48% to IR. In addition, a direct relationship of body size with CR and IR in both temperatures was observed. The effect of temperature at 22 ° C on SOC in all groups was evaluated, with an increase of 239.8, 165.3 and 183.4% for size individuals of 8.1 ± 0.351, 0.058 ± 5.6 and 4.3 ± 0.100 respectively. Furthermore, in both evaluated temperatures, the results show an indirect relationship of body size with the SOC.